1997
DOI: 10.1095/biolreprod56.5.1126
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Insulin and Insulin-Like Growth Factor-I Ovarian Receptors during the Reproductive Cycle of Carp (Cyprinus Carpio)1

Abstract: Insulin and insulin-like growth factor-I (IGF-I) receptors were characterized in glycoprotein fractions prepared by wheat germ agglutinin-agarose affinity chromatography from the ovaries of carp. Insulin-specific overall binding in carp ovaries was 6- to 11-fold lower than IGF-I binding (2.7 +/- 0.48% vs. 22.8 +/- 3.6% per 20 microg glycoprotein). Cold IGF-I displaced radiolabeled IGF-I binding in doses 1000- to 3000-fold lower than cold insulin. On the other hand, cold insulin displaced radiolabeled insulin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…This provides evidence in favour of specificity of different receptor-mediated signalling cascades at the oocyte surface. While Igf1 receptor has been purified and high affinity Igf1 binding sites were demonstrated in amphibian oocytes as well as in carp ovary (Hainaut et al 1991, Maestro et al 1997, the possibility of all four Igf ligands acting through Igf1r in zebrafish oocytes cannot be ruled out at this moment since transcripts for two Igf1 receptor isoforms (igf1ra and igf1rb) have been detected earlier (Nelson & Van Der Kraak 2010b). Moreover, immunoblot analysis reveal that while Igf1 triggers a robust increase in Akt phosphorylation (Ser473), DHP stimulation also promotes a significant increase in Akt activation as early as 15 min of in vitro incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides evidence in favour of specificity of different receptor-mediated signalling cascades at the oocyte surface. While Igf1 receptor has been purified and high affinity Igf1 binding sites were demonstrated in amphibian oocytes as well as in carp ovary (Hainaut et al 1991, Maestro et al 1997, the possibility of all four Igf ligands acting through Igf1r in zebrafish oocytes cannot be ruled out at this moment since transcripts for two Igf1 receptor isoforms (igf1ra and igf1rb) have been detected earlier (Nelson & Van Der Kraak 2010b). Moreover, immunoblot analysis reveal that while Igf1 triggers a robust increase in Akt phosphorylation (Ser473), DHP stimulation also promotes a significant increase in Akt activation as early as 15 min of in vitro incubation.…”
Section: Discussionmentioning
confidence: 99%
“…While Igfs alone can induce GVBD, Igf2 has been shown to up-regulate mPRa and resumption of meiosis providing evidence behind integration of MIS and Igf signalling (Picha et al 2012). Moreover, isolation of Igf1r and detection of high affinity Igf1 binding sites in the carp ovary (Maestro et al 1997), coupled with expression of two different Igf receptor isoforms (Igf1ra and Igf1rb) in zebrafish oocyte (Nelson & Van Der Kraak 2010b) further strengthens the possibility of direct action of Igf on oocyte membrane and regulation of final OM (Reinecke 2010). Although gonadotropin regulation of major follicular events, e.g., biosynthesis of maturational steroid as well as Igf expression might involve common cellular signalling cascades, such as cAMP/PKA and/or MEK/MAPK (Nagahama & Yamashita 2008, Li et al 2011, much less is known about interplay between these pro-maturational factors in teleost ovary.…”
Section: Introductionmentioning
confidence: 99%
“…The -subunits contain single transmembrane domains and highly conserved cytoplasmic tyrosine kinase domains (Cheatham & Kahn 1995, LeRoith et al 1995. In teleosts, ligand-binding studies using mammalian IGF-I and insulin have consistently demonstrated the presence of high-affinity binding sites on various membranes prepared from teleost tissues (Drakenberg et al 1993, Maestro et al 1997. The binding of IGF-I in teleost muscle ectotherms was abundant and at higher affinity than that of insulin, although IGF-IR mRNA was expressed at the lowest levels in rainbow trout muscle (Greene & Chen 1999a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Minimal information exists describing normal seasonal plasma levels of INS in teleosts, and few studies have revealed that circulating levels fluctuate during the reproductive cycle, presenting the highest concentrations prior to vitellogenesis [60]. The precise functions of INS during these time frames, particularly during primary ovarian growth, have been described by measuring DNA synthesis and binding receptor studies [61,62]. INS and INSlike growth factor-I (IGF-I) have been shown to bind to fish ovaries primarily in previtellogenic oocytes of carp [62], and recombinant human IGF-I increased the diameter of shortfinned eel previtellogenic oocytes [22].…”
mentioning
confidence: 99%
“…The precise functions of INS during these time frames, particularly during primary ovarian growth, have been described by measuring DNA synthesis and binding receptor studies [61,62]. INS and INSlike growth factor-I (IGF-I) have been shown to bind to fish ovaries primarily in previtellogenic oocytes of carp [62], and recombinant human IGF-I increased the diameter of shortfinned eel previtellogenic oocytes [22]. These studies support a role for INS in directing primary growth events in developing oocytes, and our data further suggest a specific role for controlling vtgr mRNA production during this window.…”
mentioning
confidence: 99%